2010
DOI: 10.1159/000317935
|View full text |Cite
|
Sign up to set email alerts
|

Cinacalcet – Clinical and Laboratory Effectiveness, Concomitant Treatment Patterns and Treatment Cost: Could We Do Better and How?

Abstract: Background: The cost and effectiveness patterns in the treatment of secondary hyperparathyroidism (SHPT) in dialysis patients in the Czech Republic are unknown. Methods: 52 dialysis patients from 17 centers were followed up in a multicenter prospective study of laboratory and clinical (hospitalization rate, clinical complaints questionnaire) responses to 12-month cinacalcet treatment. Treatment patterns and cost (including phosphate binders, vitamin D, and cinacalcet) were evaluated. Results: The mean s-Ca dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…After its approval, uptake of cinacalcet by the nephrology community was rapid [11]. However, there is a paucity of data evaluating real-world use and effectiveness of cinacalcet; existing reports provide only descriptive characterizations in mostly small patient samples [12,13,14]. Factors that predict cinacalcet initiation as well as dose titrations and discontinuation among patients who initiate therapy are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After its approval, uptake of cinacalcet by the nephrology community was rapid [11]. However, there is a paucity of data evaluating real-world use and effectiveness of cinacalcet; existing reports provide only descriptive characterizations in mostly small patient samples [12,13,14]. Factors that predict cinacalcet initiation as well as dose titrations and discontinuation among patients who initiate therapy are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…While cinacalcet has been shown in clinical trials to reduce PTH, serum calcium, and phosphorus concentrations in end-stage renal disease (ESRD) patients with SHPT [15,16,17], little available data show the degree of laboratory changes that occur under usual clinical care [12,13,14], the presumed mechanism by which some or all clinical benefit is mediated. Notable among these studies was the pan-European ECHO study (n = 1,865), which detailed achievement of biochemical targets in patients initiated on cinacalcet [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many observational and randomized controlled trials, cinacalcet has been shown to be effective in reducing serum PTH, Ca, P and Ca x P levels (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). However, there are some studies suggesting that cinacalcet treatment is less effective than it seems for reducing PTH levels and also has a high cost (19). We observed that effectiveness and compliance of cinacalcet was low during the follow-up period in our patients and we recognized that there is no data on this subject in the other centers of our country.…”
Section: Introductionmentioning
confidence: 48%
“…Cinacalcet was introduced in the year 2004 and has been proven to be effective in the treatment of secondary hyperparathyroidism [15,16] and other morbidities e.g. calciphylaxis [17].…”
Section: Discussionmentioning
confidence: 99%